Larangan Putus Asa dalam QS. Yusuf: 86-87 - Azka Noor (MAGHZA, 2021)
Despair often occurs when humans cannot achieve what they want, despair that always appears at the end, as if to signal the end of hope, of course, Allah forbids despair amid humans who still have the opportunity to try. This article explores the story of the prophet Yaqub who was always optimistic when he lost his favorite son, Prophet Yusuf. Discussed with Abdullah Saeeds hermeneutic method, the research aims to find the significance and value of optimism in the story of the prophet Yaqub recorded in Qs. Yusuf verses 86, 87. The results of this study are the story of the prophet Yaqub has an element in the form of Mauizah al-Hasanah (good advice) which was specifically given to the prophet Muhammad for later advice to his people. The significance of the story of the prophet Yaqub and the prophet Yusuf has at least three urgencies, namely the prohibition of giving up, promoting an attitude of optimism in every situation, being polite and patient when dealing with children.